2015
DOI: 10.1371/journal.pone.0136979
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Witnessing of Conspecifics in Pain: Effects on Emotional Contagion

Abstract: Witnessing of conspecifics in pain has been shown to elicit socially triggered freezing in rodents. It is unknown how robust this response is to repeated exposure to a cage-mate experiencing painful stimulation. To address this question, shock-experienced Observer rats repeatedly witnessed familiar Demonstrators receive painful footshocks (six sessions). Results confirm that Observers freeze during the first testing session. The occurrence of this behaviour however gradually diminished as the experimental sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 28 publications
2
45
0
Order By: Relevance
“…Though generally appearing in non-fearful situations, yawning has been also observed in stressful situations in different species and can serve as a possible indicator of increased stress (Aureli and de Waal, 1997; Kubota et al, 2014; Leone et al, 2014; Miller et al, 2012). In line with this hypothesis, a reduction of yawning has been observed following administration of the glucocorticoid synthesis blocker, metyrapone (Carrillo et al, 2015). However, intranasal oxytocin, believed to suppress stress and enhance empathy (Hurlemann et al, 2010), did not affect yawning per se , but increased awareness of the act in participants, which resulted in higher rate of efforts made to conceal it (Gallup and Church, 2015).…”
Section: Emotional Contagionmentioning
confidence: 72%
See 1 more Smart Citation
“…Though generally appearing in non-fearful situations, yawning has been also observed in stressful situations in different species and can serve as a possible indicator of increased stress (Aureli and de Waal, 1997; Kubota et al, 2014; Leone et al, 2014; Miller et al, 2012). In line with this hypothesis, a reduction of yawning has been observed following administration of the glucocorticoid synthesis blocker, metyrapone (Carrillo et al, 2015). However, intranasal oxytocin, believed to suppress stress and enhance empathy (Hurlemann et al, 2010), did not affect yawning per se , but increased awareness of the act in participants, which resulted in higher rate of efforts made to conceal it (Gallup and Church, 2015).…”
Section: Emotional Contagionmentioning
confidence: 72%
“…Magnitude of vicarious freezing response was modulated by previous experience with shocks (Atsak et al, 2011; Sanders et al, 2013), familiarity (Jeon et al, 2010; Gonzalez-Liencres et al, 2014), genetic background (Chen et al, 2009), and rearing conditions (Yusufishaq and Rosenkranz, 2013; Panksepp and Lahvis, 2016). Interestingly, repeated exposure to a cage mate experiencing foot shocks resulted in a gradual decrease of socially triggered freezing in the observers (Carrillo et al, 2015). It is noteworthy that vicarious fear learning is associated trait measure of empathy in humans (Kleberg et al, 2015), which indicates that the rodent models described above may tap into some fundamental features of empathy across species.…”
Section: Emotional Contagionmentioning
confidence: 99%
“…Most rodents are social animals, living substantial parts of their lives in groups of variable size and displaying a rich repertoire of social behaviors. Similar to humans and to the other animal species described above, rodents have been recently shown to be able to perceive and react to the emotional state of conspecifics, and in some cases, to produce complex pro‐social behaviors possibly related to empathy . However, research on rodent emotion recognition in settings similar to the ones described above is still underdeveloped.…”
Section: Emotion Recognition In Nonhuman Animalsmentioning
confidence: 92%
“…Conversely, an increased stress response has been found to underlie distress in social observational learning. The repeated witnessing of a conspecific in pain triggers freezing responses in rats, a behavior that eventually decreases and is replaced by spontaneous yawning (Carrillo et al, 2015). In this context, yawning is hypothesized to reflect increased distress and a coping strategy.…”
Section: Emotional Contagion: Social Modulation Of Fear and Painmentioning
confidence: 99%
“…Yawn contagion has been reported to occur in a variety of species including humans, bonobos, chimpanzees, parrots, and dogs (Demuru and Palagi, 2012;Massen et al, 2012;Miller et al, 2012;Romero et al, 2013) and susceptibility to contagious yawning is correlated with social familiarity (Demuru and Palagi, 2012;Romero et al, 2013). Interestingly, rats are known to yawn and in some situations yawning is considered a sign of distress (Carrillo et al, 2015). The neuropeptide oxytocin, known for its role in social communication and bonding (Bartz et al, 2010;Rodrigues et al, 2009b) has been shown to induce yawning in male rats (Sanna et al, 2012).…”
Section: Emotional Contagion: Social Modulation Of Fear and Painmentioning
confidence: 99%